Anthropological analysis of projectile trauma to the bony regions of the trunk - Humphrey, Caitlin; Henneberg, Maciej (Anthropological Review, 2017)
Ballistics literature often focuses on soft tissue injures and projectile trauma to the cranium. Minimal details on the bony characteristics of projectile trauma to the thorax/abdomen regions have been published. This study aims to analyse projectile trauma to the bony trunk region including the ribs, vertebrae, scapula, sternum and the hip bone to form a better understanding of the characteristics and biomechanics of skeletal trauma caused by a projectile and contribute to the existing database on skeletal trauma caused by projectiles. Fourteen cases of documented projectile trauma to the bony regions of the trunk from the Hamman-Todd Human Osteological Collection at the Cleveland Natural History Museum, Ohio were analysed. Of the 14 individuals with gunshot wounds examined, 40 wounds occurred to the bones. Twenty-four injuries to the ribs, 1 ilium, 11 vertebrae, 3 scapulae, and 1 sternum. Fracture patterns, heaving and bevelling can be used to determine the direction of travel of the projectile which can be evident on the ribs, sternum, scapula and ilium. It is critical to understand the wounding patterns associated with projectile trauma to the torso region as this is often targeted, due to being the centre of mass.